The Influence of Outpatient Health Services on the Satisfaction of Health BPJS Participants at the Huraba Health Center, Angkola Timur Sub-District in 2023 - Erika Maryanti Harahap; Juliandi Harahap; Yuniati Yuniati (Universitas Ibn Khaldun Bogor, 2024)
This study analyzes the impact of outpatient health services on the satisfaction of BPJS Health participants at the Huraba Community Health Center, East Angkola District in 2023. Factors including responsiveness, reliability, guarantee, care, and physical evidence of service are explored to determine their influence on patient satisfaction. The research method used is quantitative with a cross sectional study approach. Primary data was collected through questionnaires distributed to patients, while secondary and tertiary data were obtained from documentation and trusted sources. The results of the analysis show that the aspects of responsiveness, reliability, assurance and caring have a significant influence on patient satisfaction, while physical evidence does not show a strong correlation.